Exploring early termination patterns and effectiveness of trauma-focused cognitive behavioral therapy for children in foster care. (April 2023) - Esterer, Madeline; Carlson, John S.; Roschmann, Sarina; Kim, HaeDong; Cowper, Amy; Cranmer-Fosdick, Holly; Ludtke, Mary; DeCicco, Barry
Highlights: Trauma-focused cognitive behavioral therapy benefits foster care youth. Day-to-day functioning and post-traumatic stress symptoms improve with treatment. Older child age and home-based care may indicate a higher risk for termination. Abstract: Children in foster care experience trauma at a high rate, resulting in their need for effective and accessible mental health treatments. Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) has the potential to significantly improve the functional impairment and post-traumatic stress symptoms (PTSS) of children in foster care who fully complete treatment without terminating early. The purpose of this study was to explore child- and setting-level predictors (age, sex assigned at birth, race and ethnicity, treatment setting, and pre-treatment level of post-traumatic stress symptoms) of early termination and multifaceted TF-CBT effectiveness outcomes within a statewide practice initiative ( N  = 399). Accessibility and completion of TF-CBT within this sample of children in foster care were measured by early termination rates. Older children (7.8% more likely) and those receiving home-based TF-CBT (57.1% more likely) terminated TF-CBT early at significantly higher rates. No differences in treatment completion were found for race and ethnicity, sex assigned at birth, or pre-treatment PTSS. Results support that TF-CBT can improve PTSS and associated functional impairment at a degree that is statistically and clinically significant for children in foster care. Implications of study findings for TF-CBT treatment of foster care youth who are older and receiving home-based care are provided.